2007
DOI: 10.1016/j.jasms.2006.09.027
|View full text |Cite
|
Sign up to set email alerts
|

A study of noncovalent complexes involving single-stranded DNA and polybasic compounds using nanospray mass spectrometry

Abstract: Noncovalent complexes involving a single-stranded DNA oligonucleotide and a polybasic compound (spermine, penta-L-lysine, penta-L-arginine, or polydisperse poly-L-lysine) were detected by nanospray-MS. Several control experiments tended to show that these complexes preexisted in solution and that the interactions were initially ionic ones between oligonucleotide phosphates and protonated basic sites of the polybasic compound. Collision-induced dissociation (CID) experiments carried out with these complexes all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
4
16
1
Order By: Relevance
“…However, speed and ease of use of MALDI-TOF MS support its use for this kind of study. In a previous ESI-MS report [7], it has been shown that Coulomb repulsions could have an influence on the stability of the multiply charged complexes. The production of singly charged species might be another important advantage of MALDI over the electrospray technique.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, speed and ease of use of MALDI-TOF MS support its use for this kind of study. In a previous ESI-MS report [7], it has been shown that Coulomb repulsions could have an influence on the stability of the multiply charged complexes. The production of singly charged species might be another important advantage of MALDI over the electrospray technique.…”
Section: Discussionmentioning
confidence: 98%
“…ESI-MS is generally recognized as the method of choice for the study of noncovalent complexes [6]. However, to our knowledge, this technique has not been used to survey complexes between DNA and polybasic compound until a recent report from our group [7]. Nevertheless, several works by ESI-MS focused on related systems in which two peptides formed a noncovalent complex by ionic bonds [8 -11].…”
mentioning
confidence: 99%
“…Many of these interactions are facilitated through arginine–phosphate recognition. Indeed the arginine moiety mediates many biological noncovalent events, including protein/metal, protein/protein, protein/peptide, and protein/oligonucleotide interactions 7678. Phosphorylation and dephosphorylation of amino acid residues in serine, threonine and tyrosine govern numerous biochemical and physiological processes 79.…”
Section: Binding To Single-stranded Dnamentioning
confidence: 99%
“…Two dissociation pathways were observed for the complex: disruption of the electrostatic interactions between the Arg residues and the phosphate groups, and separation of the peptides with concurrent dissociation of the C-O side-chain covalent bond and transfer of HPO 3 from either pT or pSi to the basic peptide. Terrier et al recently reported a study of noncovalent complexes involving single-stranded DNA and polybasic compounds, including poly-lysine and penta-arginine [51]. For some of the complexes, MS/MS of the DNA-polybasic complex yielded fragmentation of DNA covalent bonds and an oligonucleotide fragment remain bound to the polybasic compound.…”
Section: Unusual Stability Of Gas Phase Charge-charge Interactionsmentioning
confidence: 99%